Measuring the Efficiency Performance of Rural Banks in East Java during Covid-19 : A Novel Approach using SuperDEA - Aisyah As-Salafiyah (Accounting and Sustainability, 2023)
This research aims to analyze the efficiency level, source of efficiency, the potential for improvement needed, and comparison of the efficiency of BPR (Rural Bank) and BPRS (Islamic Rural Bank) in East Java. This research also looks at the efficiency of BPR and BPRS during the Covid-19 pandemic. The research period used in this study is from 2016-2021, with a research sample of 8 BPR and 6 BPRS in East Java. The analytical method used is a non-parametric approach, namely Data Envelopment Analysis (DEA), with secondary data sources originating from BPR and BPRS financial reports on the official OJK website. The study results show that the efficiency of BPR and BPRS during 2016-2021 has fluctuated yearly. BPR has higher efficiency than BPRS. Then in the efficiency analysis during the pandemic, the efficiency of BPR is relatively stable, even though there has been a decline in 2021. Meanwhile, BPRS showed a significant decline in 2021. Furthermore, based on the potential improvement analysis, the most significant cause of BPR inefficiency comes from input variables, namely fixed assets, and at BPRS is the financing provided. This research also provides recommendations to banks, regulators, and academics.